Percutaneous Image-Guided Cryoablation of Metastatic Colorectal Adenocarcinoma to the Abdominal Wall - Drogin, Jillian; Abdelbaki, Ahmed; Lendermon, Justin; Pereira, Keith; Mendez-Castillo, Alejandro (The Arab Journal of Interventional Radiology, 2023)
Abdominal wall metastases are rarely seen in primary colorectal cancer; the majority of cases are attributed to seeding from previous procedures. We report a case of percutaneous cryoablation of metastatic colorectal cancer to the abdominal wall with no evidence of recurrence 1 year later.
Keywords: abdominal wall; cryoablation; metastasis